The Association Between Long-Term Exposure to Particulate Matter and Incidence of Hypertension Among Chinese Elderly: A Retrospective Cohort Study - Wensu, Zhou; Wen, Chen; Fenfen, Zhou; Wenjuan, Wang; Li, Ling (Frontiers in Cardiovascular Medicine, 2022)
Background and Objectives: Studies that investigate the links between particulate matter ≤2. 5 μm (PM2.5) and hypertension among the elderly population, especially those including aged over 80 years, are limited. Therefore, we aimed to examine the association between PM2.5 exposure and the risk of hypertension incidence among Chinese elderly. Methods: This prospective cohort study used 2008, 2011, 2014, and 2018 wave data from a public database, the Chinese Longitudinal Healthy Longevity Survey, a national survey investigating the health of those aged over 65 years in China. We enrolled cohort participants who were free of hypertension at baseline (2008) from 706 counties (districts) and followed up in the 2011, 2014, and 2018 survey waves. The annual PM2.5 concentration of 706 counties (districts) units was derived from the Atmospheric Composition Analysis Group database as the exposure variable, and exposure to PM2.5 was defined as 1-year average of PM2.5 concentration before hypertension event occurrence or last interview (only for censoring). A Cox proportional hazards model with penalized spline was used to examine the non-linear association between PM2.5 concentration and hypertension risk. A random-effects Cox proportional hazards model was built to explore the relationship between each 1 μg/m3, 10 μg/m3 and quartile increment in PM2.5 concentration and hypertension incidence after adjusting for confounding variables. The modification effects of the different characteristics of the respondents were also explored. Results: A total of 7,432 participants aged 65–116 years were enrolled at baseline. The median of PM2.5 exposure concentration of all the participants was 52.7 (inter-quartile range, IQR = 29.1) μg/m3. Overall, the non-linear association between PM2.5 and hypertension incidence risk indicated that there was no safe threshold for PM2.5 exposure. The higher PM2.5 exposure, the greater risk for hypertension incidence. Each 1 μg/m3 [adjusted hazard ratio (AHR): 1.01; 95% CI: 1.01–1.02] and 10 μg/m3 (AHR: 1.12; 95% CI: 1.09–1.16) increments in PM2.5, were associated with the incidence of hypertension after adjusting for potential confounding variables. Compared to first quartile (Q1) exposure, the adjusted HRs of hypertension incidence for the Q2, Q3 and Q4 exposure of PM2.5 were 1.31 (95% CI: 1.13–1.51), 1.35 (95% CI: 1.15–1.60), and 1.83 (95% CI: 1.53–2.17), respectively. The effects appear to be stronger among those without a pension, living in a rural setting, and located in central/western regions. Conclusion: We found no safe threshold for PM2.5 exposure related to hypertension risk, and more rigorous approaches for PM2.5 control were needed. The elderly without a pension, living in rural and setting in the central/western regions may be more vulnerable to the effects of PM2.5 exposure.